2019
DOI: 10.1002/nag.2905
|View full text |Cite
|
Sign up to set email alerts
|

On the rheological characterisation of liquefied sands through the dam‐breaking test

Abstract: Summary This paper concerns the rheological characterisation of liquefied sands as non‐Newtonian Bingham fluids. For this purpose, dam‐breaking laboratory tests are often executed and interpreted, offering a viable option to identify the properties of fluidised water‐soil mixtures. However, limited attention has been devoted so far to clarify what variables and measurements would allow unambiguous calibration of Bingham parameters, namely, the viscosity η and the yield stress τy. The numerical results of param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…17to represent the behaviour of frictional viscoplastic materials. This model has been extensively used in the PFEM framework to simulate the flow of soil or granular material in [22,61,117].…”
Section: Rheological Lawmentioning
confidence: 99%
“…17to represent the behaviour of frictional viscoplastic materials. This model has been extensively used in the PFEM framework to simulate the flow of soil or granular material in [22,61,117].…”
Section: Rheological Lawmentioning
confidence: 99%
“…The analyses given in Basic et al [37] have shown that the types of problems described using Equations ( 17) and ( 19) reach second-order convergence for Dirichlet, Neumann and mixed-boundary conditions. Equation (19), along with the no-slip boundary condition, can be straightforwardly solved using an iterative matrix-free solver.…”
Section: Numerical Solvermentioning
confidence: 99%
“…Two-and three-dimensional simulations were carried out using the PFEM, and solid structures were simulated by employing FEM. Della Vecchia et al [19] investigated Bingham fluids, specifically the rheological characteristics of water-soil mixtures on the dam-break tests. The numerical analysis examined the viscosity and yield stress of the Bingham model based on the CFD-PFEM parametric studies.…”
Section: Introductionmentioning
confidence: 99%
“…According to Montassar and de Buhan (2013), "obtained data for the equivalent Newtonian viscosity coefficients range between 10 −1 and 10 7 Pa•s". Not only 'intrinsic' factors (e.g., soil mineralogy, porosity, and grain size distribution) contribute to such variability, but also the lack of standard procedures for the interpretation of laboratory tests (Della Vecchia et al, 2019).…”
Section: Rheology Of Liquefied Sandmentioning
confidence: 99%